ON THE METHODICS OF MATHEMATICAL MODELLING OF POLLUTION OF HYDROLITHOSPHERE BY PETROLEUM PRODUCTS (EXEMPLIFIED BY KURSK OIL TERMINAL) - Bredikhin, Vladimir Viktorovich; Khaustov, Vladimir; Melkumov, Dmitriy (Journal of Applied Engineering Science, 2021)
A potential threat of pollution of hydrolithosphere with petroleum and its products due to accidental and technological leaks on a certain industrial object has been analyzed. The author's method of mathematical modelling is described that allows to perform an adequate dynamic modelling of a petroleum products lens in an aquifer. Execution of the resulting model allows to forecast behavior of petroleum products in the conditions of a real geological and hydro-geological cross-section.
Keywords: petroleum products, lithosphere pollution, petroleum lens, mathematical model, groundwater movement, prognosis.